(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The crisis of identity is one of the major issues of mankind.It does not confine to any single country, region, religion or ethnic group. Identity crisis prevails all over the world. It is also not confined to any particular age group people though the identity problem is predominantly visible in the life of younger generation. When we concentrate on the crisis of identity in Indian context, it has become the major problem of current educated youth. So far, many writers of fiction have focused on the identity problem and Chetan Bhagat is no exception on this list. Since identity crisis, mostly, seems to be the major problem of the age group people between 18 to 30, Bhagat has appropriately dealt with it in his fiction. The educated younger generation, in general, face problems to get well settled in life after completion of their education.The students, now-a-days, have been facing numerous problems in their academic career itself to beat the crisis. Chetan Bhagat as a young entertainer, attempts to depict all their problems in his fiction. The problems include Mindless mugging (No room for creativity and Innovativeness), lack of Disciplinary Ethics, Rigidity, Monotony in Academic work, Students’ Unrest, Fear, Insecurity, Controlled Stress and Suicide under Parental and Academic Pressure etc. For the purpose of my paper, I have chosen to study the identity problem crisis in youth of contemporary Indian Society and its portrayal in Chetan Bhagat’s maiden novel, Five Point Someone-What not to do at IIT.